2020
DOI: 10.1177/0145561320965208
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Factors in Obstructive Sleep Apnea: A Systematic Review With Meta-Analysis

Abstract: Background: Previous studies revealed that the prothrombotic factors in patients with obstructive sleep apnea (OSA) remain controversial. Aim/Objective: The aim of the systematic review is to elucidate the relationship between prothrombotic factors and OSA. Materials and Methods: This systematic review was performed under the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. The literature we investigated was extracted from 4 main medical databases (PubMed, Web of Science, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Saygin et al found a positive correlation between the PLT count and the severity of OSA in adult patients with CVD, which meant that PLT count was considered an independent risk factor for CVD in adults with OSA [15]. However, no correlation between PLT count and adults with OSA without any comorbidities was observed in some studies [16][17][18]. In the limited studies about PLTs in children with OSA, there are conflicting conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Saygin et al found a positive correlation between the PLT count and the severity of OSA in adult patients with CVD, which meant that PLT count was considered an independent risk factor for CVD in adults with OSA [15]. However, no correlation between PLT count and adults with OSA without any comorbidities was observed in some studies [16][17][18]. In the limited studies about PLTs in children with OSA, there are conflicting conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma fibrinogen levels were elevated in patients with OSA in most [87][88][89] but not all studies [90]. In a recent meta-analysis on prothrombotic markers including 2190 participants from 15 studies, patients with OSA had significantly higher plasma fibrinogen levels compared with controls [9]. Wessendorf et al demonstrated that elevated circulating fibrinogen was associated with the severity of OSA in patients with concomitant history of stroke suggesting a possible link between OSA-associated hypercoagulation and cerebrovascular complications [89] (Supplementary Table S1).…”
Section: Current Knowledge On the Effects Of Osa On Coagulation Fibrmentioning
confidence: 99%
“…Several studies have reported that fibrinogen and other prothrombotic factors are increased and that fibrinolytic capacity is reduced in OSA. Endothelial dysfunction, an increase in prothrombotic factors [9], a decrease in fibrinolytic activity, platelet activation, and changed rheology and viscosity (e.g., increase in haematocrit as a consequence of nocturnal hypoxaemia) are potential mechanisms explaining a prothrombotic state in OSA [10]. Although there are several convincing theories for how the pathophysiological consequences of OSA might result in a procoagulant state, either via endothelial dysfunction or through interfering with the coagulation cascade or fibrinolysis, there is only limited quality evidence on a direct causative relationship between OSA and a procoagulant state.…”
Section: Introductionmentioning
confidence: 99%